2016
DOI: 10.4103/0976-237x.188552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulpal response of deciduous teeth after direct pulp capping with bioactive glass and mineral trioxide aggregate

Abstract: Aim:The aim of this study was to evaluate the pulpal response of primary teeth after direct pulp capping (DPC) with two biocompatible materials namely mineral trioxide aggregate (MTA) and bioactive glass (BAG).Settings and Design:This study was a randomized clinical trial.Materials and Methods:A total of 22 healthy primary canine teeth scheduled for extraction for orthodontic reasons were selected. The teeth were divided into two groups of 11 and underwent DPC. The exposure sites were randomly capped with MTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The findings of our study are in harmony with some recent clinical trials on the DPC of primary molars. 4 , 21 , 22 , 36 Despite the highly populated mesenchymal cell content of primary molars, the DPC can be a successful conservative treatment if proper case selection is followed, a favorable pulp material is used and the correct procedure is meticulously adhered. However, further clinical trials with longer follow-up periods and larger samples sizes, along with more histological investigations into the material characteristics of this novel cement, seem relevant to derive more definitive conclusions on the successful use of protooth cement for the DPC of primary molars.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study are in harmony with some recent clinical trials on the DPC of primary molars. 4 , 21 , 22 , 36 Despite the highly populated mesenchymal cell content of primary molars, the DPC can be a successful conservative treatment if proper case selection is followed, a favorable pulp material is used and the correct procedure is meticulously adhered. However, further clinical trials with longer follow-up periods and larger samples sizes, along with more histological investigations into the material characteristics of this novel cement, seem relevant to derive more definitive conclusions on the successful use of protooth cement for the DPC of primary molars.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with microsized particles, nBGs generate a faster release of soluble ions, which are capable of chemically driving hDPSCs along a mineralization pathway [68]. In addition, the application of microsized BG in a pulp capping procedure in primary human teeth has been shown to promote dentin bridge formation [58].…”
Section: Discussionmentioning
confidence: 99%
“…The specific use of BG in VPT has been explored in animal models, showing the formation of reparative dentin and only mild inflammatory response in pulp capping procedures [55][56][57]. More recently, in a clinical trial on primary teeth, it demonstrated the formation of a dentin bridge [58]. However, there are no commercially available materials with BG currently, nor with nBGs for VPT application.…”
Section: Introductionmentioning
confidence: 99%
“…Pulpotomy is the treatment of choice for primary teeth with pulp involvement due to extensive carious lesions. [ 1 2 ] Formocresol is commonly used for pulpotomy of primary teeth through devitalization of dental pulp. After devitalization of dental pulp with formocresol, several materials can be used for capping of the remaining pulp tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is the treatment of choice for primary teeth with pulp involvement due to extensive caries. [ 1 2 ] Pulpotomy is performed through three methods, namely, devitalization, preservation, and remineralization. Several materials are also used for pulpotomy of teeth.…”
Section: Introductionmentioning
confidence: 99%